The historicity of the circle of the Twelve: All roads lead to Jerusalem 1 - Aarde, Andries van (Hervormde teologiese studies, 1999)
The aricle consists ofive argumentaive sections. The first deals with the textual evidence with regard to the expressions "disciples", "the Twelve" and "apostles". In the second section it is argued that Jesus did not create the idea of "the Twelve". Firstly, the argument focuses on a discussion of the differences and similarities in the lists of twelve names found in the synopic gospels, Acts and the Sayings Gospel Q and, secondly, of the so-called "minor agreement" between Mathew (19:28) and Luke (22:30) with regard to the expressions the "twelve thrones" and the "twelve tribes of Israel". The investigation concludes that all roads lead to Jerusalem with regard to the historicity of the circle of the Twelve. Section three discusses the situaion in pre-70 CE Jerusalem where the earliest Jesus faction linked the idea of "the Twelve" with there surrection of Jesus and the appearances tradition. It is argued that the appearances tradition coincides negaively with an endeavour among leaders of the Jesus movement to seek positions of power and, positively, with the spread of the gospel to people who were previously considered to be excludedfrom being children of God.